Carbon dioxide utilisation: unlocking enhanced properties for oxygenated polymers - Poon, KC (2024)
This thesis describes the synthesis of new oxygenated plastics and elastomers from CO2 and bio-derived feedstocks, where non-covalent cross-linking interactions between chains are employed to improve and tune thermomechanical properties. Networks are established through reversible metal-ligand bonding, macromolecular entanglements, and thiol-ene crosslinking during vat photopolymerization 3D printing. This thesis aims to develop strategies to improve the thermomechanical properties of CO2-derived polymers, to match those of the current petrochemical incumbents. Chapter 1 provides an introduction to the latest progress in the development of sustainable and oxygenated plastics and elastomers. Specifically, polyesters and polycarbonates produced through lactone ring-opening polymerisation and epoxide/CO2 ring-opening copolymerisation to form high molar mass homopolymers and ABA triblock polymers. The potential of macromolecular networking strategies and the chemistries to facilitate non-covalent interactions are discussed. Chapter 2 reports new CO2-derived thermoplastic elastomers (TPEs) together with a generally applicable method to augment tensile mechanical strength and Young's modulus without requiring material re-design. These TPEs combine high glass transition temperature (Tg) amorphous blocks comprising CO2-derived poly(carbonates) (A-block), with low Tg poly(ε-decalactone), from castor oil, (B-block) in ABA structures. The poly(carbonate) blocks are selectively functionalized with metal-carboxylates, where the metals are Na(I), Mg(II), Ca(II), Zn(II) and Al(III). The colorless polymers, featuring <1 wt% metal, show tunable thermal (Tg), and mechanical (elongation at break, elasticity, creep-resistance) properties. The best elastomers show >50-fold higher Young's modulus and 21-times greater tensile strength, without compromise to elastic recovery, compared with the starting block polymers. They have wide operating temperatures (-20 to 200 °C), high creep-resistance and yet remain recyclable. Chapter 3 describes well-defined, high molar mass CO2 terpolymers prepared from cyclohexene oxide (CHO), cyclopentene oxide (CPO), and CO2 by using a [Zn(II)Mg(II)] catalyst. In the catalysis, CHO and CPO show reactivity ratios of 1.53 and 0.08 with CO2, respectively; as such, the terpolymers have gradient structures. The poly(cyclohexene carbonate)-grad-poly(cyclopentene carbonate) (PCHC-grad-PCPC) have high molar masses (Mn >86 kg mol-1) and good thermal stability (Td > 250 °C). All the polymers are amorphous with a single, high glass transition temperature (96 < Tg < 108 °C). The polymer entanglement molar masses, determined using dynamic mechanical analyses, range from 4 < Me < 23 kg mol-1 depending on the polymer composition (PCHC:PCPC). These polymers show superior mechanical performance to PCHC; specifically, the lead material (PCHC0.28-grad-PCPC0.72) shows 25% greater tensile strength and 160% higher tensile toughness. These new plastics are recycled, using cycles of reprocessing by compression moulding, four times without any loss in mechanical properties. They are also efficiently chemically recycled to selectively yield the two epoxide monomers, CHO and CPO, as well as carbon dioxide, with high activity (TOF = 270-1653 h-1). The isolated recycled monomers are repolymerized to form a thermoplastic showing the same material properties. Chapter 4 reports the successful additive manufacturing of a series of poly(carbonate-b-ester-b-carbonate) elastomers, derived from carbon dioxide and bio-derived ε-decalactone. By employing a highly active and selective [Co(II)Mg(II)] polymerisation catalyst, an ABA triblock copolymer (Mn = 6.3 kg mol-1, ÐM = 1.26) was synthesised on a 200 g scale, formulated into resins which were 3D printed using digital light processing (DLP), and a thiol-ene-based crosslinking system. A series of elastomeric and degradable thermosets were produced, with varying thiol cross-linker length and poly(ethylene glycol) content, to produce complex triply periodic geometries at high resolution. Thermomechanical characterisation of the materials reveals printing-induced microphase separation and tunable hydrophilicity. These findings highlight how utilising DLP can produce sustainable materials from low molar mass polyols quickly and at high resolution. The 3D printing of these functional materials may help to expedite the production of sustainable plastics and elastomers with potential to replace conventional petrochemical-based options. Chapter 5 concludes the thesis and discusses future work to build on and extend the research. Chapter 6 provides the experimental details for Chapters 2-4. Chapter 7 is an appendix containing all supplementary information, figures, schemes, and tables that supports the results reported and discussed in Chapters 2-6.